Carcinogen-mediated amplification of viral DNA sequences in simian virus 40-transformed Chinese hamster embryo cells. - Lavi, S (1981)
Exposure of simian virus 40 (SV40)-transformed Chinese hamster embryo cells to various chemical and physical carcinogens induced SV40 DNA synthesis. Although the carcinogen-mediated amplification of SV40 DNA is regulated by the viral A gene, the induction of viral DNA synthesis does not result in the rescue of infectious virus or the formation of complete viral DNA molecules. Instead, a heterogeneous collection of DNA molecules containing SV40 sequences was generated by treatment with 7,12-dimethylbenz[a]anthracene. Restriction enzyme analysis of the amplified DNA molecules in the Hirt supernatant showed that not all sequences in the integrated SV40 inserts are present. The possibility that amplification of SV40 sequences is a reflection of a general-gene-amplification phenomenon mediated by carcinogens is discussed.